A multi-product strategy for the fractionation of corn stover based on peracetic acid and maleic acid processing. Issue 6 (December 2022) - Lyu, Qian; Chen, Xueli; Li, Wenxi; Zhang, Yuxuan; Xiao, Ao; Chen, Jiayi; Han, Lujia; Zhou, Chengfeng; Xiao, Weihua
Abstract: As an efficient lignocellulose fractionation process, peracetic acid and maleic acid (PAM) pretreatment is integrated into a multi-product platform for the simultaneous manufacture of cellulose, lignin, and xylose. Employing such strategy, 100 g corn stover (dry basis) yielded 39.63 g cellulose-rich solids along with 11.88 g xylose and 12.00 g lignin recovered from the pretreatment liquor. The recovery of xylose and lignin was assessed with various organic solvents, of which 2-methyltetrahydrofuran (2-MeTHF) showed superior performance, giving high lignin yield (75.23%) and xylose yield (67.32%). The recovered lignin (2-MeTHF-L) was characterized by high purity, relatively low molecular weight, and large numbers of carboxyl group. Besides, 2D-HSQC NMR analysis revealed that the 2-MeTHF-L was esterified with maleic acid during PAM pretreatment, partly responsible for its enhanced antioxidant ability. This strategy maximizes feedstock utilization and improves the processability in downstream valorization, offering a prospect for sustainable and efficient biorefineries. Graphical Abstract: ga1 Highlights: A multi-product strategy was evaluated for the fractionation of corn stover. High lignin yield (75.23%) and xylose yield (67.32%) were attained with 2-MeTHF. Recovered lignin possessed desirable properties such as low molecular weight. Esterification of recovered lignin partly enhanced the antioxidant activity.